The Effect of Accounting Information System Service Quality, Technological Innovation, and Financial Literacy on Investment Decision Making in MSMEs in Indonesia - Loso Judijanto; Eko Sudarmanto; Eva Yuniarti Utami; Darman Darman; Samalua Waoma (West Science Accounting and Finance, 2024)
This research investigates the multifaceted determinants influencing investment decision-making in Micro, Small, and Medium Enterprises (MSMEs) in Indonesia. Employing a quantitative approach, a sample of 150 participants, including owners, managers, and decision-makers, was surveyed to explore the interplay between Accounting Information System Service Quality (AISSQ), Technological Innovation (TI), Financial Literacy (FL), and their collective impact on investment decisions. Results indicate robust positive relationships between AIS service quality, financial literacy, technological innovation, and investment decision-making. The combined effect of these factors explains a substantial portion of the variance in the model (R^2 = 0.602). Practical and policy implications are discussed, offering insights to empower MSMEs in navigating dynamic economic landscapes.